Wing spot in a tropical and a temperate drosophilid: C = C enrichment and conserved thermal response - Divita Garg; Harshad Vijay Mayekar; Sanjeev Paikra; Monalisa Mishra; Subhash Rajpurohit (BMC Ecology and Evolution)
Abstract Wings are primarily used in flight but also play a role in mating behaviour in many insects. Drosophila species exhibit a variety of pigmentation patterns on their wings. In some sexually dimorphic Drosophilids, a pigmented spot pattern is found at the top-right edge of the male wings. Our understanding of wing spot thermal plasticity in sexually dimorphic species is limited with wing spots being primarily associated with sexual selection. Here, we investigated the wing pigmentation response of two species with wing spots: D. biarmipes and D. suzukii species to thermal variation. We exposed freshly hatched larvae of both the species to three different growth temperatures and checked for wing pigmentation in adult males. Our results indicate wing pigmentation is a plastic trait in the species studied and that wing pigmentation is negatively correlated with higher temperature. In both species, wings were darker at lower temperature compared to higher temperature. Further, D. suzukii exhibits darker wing pigmentation compared to D. biarmipes. Variation in wing pigmentation in both D. suzukii and D. biarmipes could reflect habitat level differences; indicating a strong G*E interaction. Raman spectral analysis indicated a shift in chemical profiles of pigmented vs. non-pigmented areas of the wing. The wing spot was found enriched with carbon-carbon double-bond compared to the non-pigmented wing area. We report that C = C formation in spotted area is thermally controlled and conserved in two members of the suzukii subgroup i.e. D. biarmipes and D. suzukii. Our study indicated a conserved mechanism of the spot formation in two Drosophila species coming from contrasting distribution ranges. Graphical Abstract